Italian as lingua franca, the law of connected vessels and the improvement of the results into the multilingual class. About a teaching experience - Alessia Terrusi (Firenze University Press, 2016)
This contribution takes cue from a teaching experience of Italian L2 to A1-level immigrant students within the SPRAR project in Lucca from November 2015 to May 2016. During lessons, the class has been enriched with students from different places in the world and who talked very different languages. Multilingualism had only one underlying theme: the Italian language used during the lessons. It was the same Italian language which they got accustomed to by living in Italy since about a year. The experience started from the hard fact that the only common knowledge was this basic-level Italian language. So a new strategy was tested: to create couples or small groups made up with students linguistically different (like anglophones with francophones). They were forced to use Italian language and let other students understand through their previous knowledges due to the daily contact with the Italian reality. This brought very positive results such as the creation of discussions about the activities, the mutual correction of mistakes, the increase of communication skills through alternative strategies (like mime or drawing). Despite the different individual and initial levels, Italian language as lingua franca let them understand Italian language more efficiently. L'italiano come lingua franca, il principio dei vasi comunicanti e il miglioramento dei risultati nella classe plurilingue. Un'esperienza didattica Il presente contributo trae spunto da un'esperienza di insegnamento di italiano L2, livello A1, a immigrati adulti all'interno del progetto SPRAR (Sistema di Protezione per Richiedenti Asilo e Rifugiati) di Lucca svoltasi tra novembre 2015 e maggio 2016. Il gruppo di corsisti era formato da adulti provenienti da diverse zone del mondo e parlanti lingue distanti tra loro. Tutti vivevano in Italia da circa un anno e poiché l'unica conoscenza comune e di eguale livello era proprio quella - basilare - dell'italiano, si è sperimentata la strategia di formare coppie o piccoli gruppi di studenti linguisticamente distanti (ad esempio francofoni e anglofoni) in modo da sollecitare l'uso delle conoscenze pregresse dovute al contatto quotidiano con la realtà italiana. Ciò ha portato a risultati più che positivi: dibattiti relativi alle attività svolte, correzione tra pari degli errori, un'incrementata capacità di farsi comprendere utilizzando strategie alternative (il mimo, il disegno). Nonostante i diversi livelli iniziali, l'uso dell'italiano come lingua franca ha permesso di far apprendere l'italiano stesso in maniera più efficace e omogenea.